Peruvian Archaeology : a Critical History. - Tantaleán, Henry (Left Coast Press, 2014)
This book offers a unique, critical perspective on the history of Peruvian archaeology by a native scholar. Leading Peruvian archaeologist Henry Tantaleán illuminates the cultural legacy of colonialism beginning with "founding father" Max Uhle and traces key developments to the present. These include the growth of Peruvian institutions; major figures from Tello and Valcárcel to Larco, Rowe, and Murra; war, political upheaval, and Peruvian regimes; developments in archaeological and social science theory as they impacted Andean archaeology; and modern concerns such as heritage, neoliberali.